(untitled) (Third Sector Social Economic Review, 2017)
Today, economics has begun to regard ""entrepreneurship"" and ""entrepreneurs"" as a fundamental factor of production in the production process. Historically, activities aimed at improving enterprise culture based on the development policies of countries have begun to gain importance in order to reach goals targeted in market economies. In this regard, Japan and South Korea experiences are emerging as remarkable examples. Even if these countries have started to go through development process late, they have made progress, improving entrepreneurship culture by way of cooperations in different fields under different corporate structures. Consequently, the improvement process of the countries aforesaid, can be qualified as “entrepreneurship based on team formation”. This process has started to manifest itself in developing countries, in which Turkey ranked, in connection with that of globalization too. In the open economies, in the face of vitality of scale-up with enterprises owing to global competition, it has been expected that entrepreneurs operating in different fields of activity or in the same field, will have joined forces with each other, whereby competitive capacity of the country would be likely to grow stronger. Thus, in this paper the development of corporate structure of Kuyumcukent Gayrimenkul Yatırımları A.S. (KUYAS) being epitomic for that process, has been handled as case study. There is a notion relevant to developing countries, in which Turkey ranked, provided by the case of KUYAS. The first of these, bringing entrepreneurs close together to serve purpose of speeding accumulation of capital up, paves the way for processes such as incorporation and governance. Latter, it ensures participation of company’s internal funds with saving function to capital accumulation process. In other words, it ensures increase of national savings. Within this scope, in this paper it was also put forth that corporate governance and improvement of corporate culture within companies would make a big contribution to accumulation of capital.